A case study on the management of UTM new hostel based on design and build arrangement [compact disc] - 374953 Nurul Hidayati Mohamed (Skudai : Universiti Teknologi Malaysia, 2005)
Thesis (Sarjana Sains (Pengurusan Pembinaan)) - Universiti Teknologi Malaysia, 2005